Does microcycle length influence the external and internal load in professional female soccer players? - Posse-Álvarez, M.; Solleiro-Duran, D.; Lorenzo-Martínez, M.; Iglesias-Soler, E.; Oliva-Lozano, J. M.; Padrón-Cabo, A. (Biology of Sport, 2025)
This study aimed to analyze the effects of microcycle length on external and internal load during training sessions and official matches in a professional female soccer team. A total of 32 microcycles were monitored for 20 outfield players using a portable 10 Hz GPS device. Microcycles were categorized by length as short (5-6 days), regular (7 days), or long (8-9 days). Training load during the microcycles was analyzedrelative to the days before or after the match day (MD), considering the following sessions: MD+1, MD-4, MD-3, MD-2, and MD-1. The external load was assessed according to total distance (TD), high-intensity running distance (HIR), sprint distance (SPD), and number of high-intensity accelerations (ACC) and decelerations (DEC). Internal load was measured using the rating of perceived exertion (RPE) and session RPE (s-RPE). The results of linear mixed model analyses showed that TD (d = 1.24-1.35), ACC (d = 0.64-0.66), and DEC (d = 0.90-1.04) were significantly higher on MD+1 in short microcycles compared to regular and long microcycles. On MD-4, large differences were observed between long and short microcycles for TD (d = 1.60), ACC (d = 1.28), DEC (d = 1.28), RPE (d = 1.25), and s-RPE (d = 1.61). Similarly, MD-3 of long microcycles showed significantly higher TD (d = 1.25-1.32), HIR (d = 1.18-1.32), and SPD (d = 0.84-1.68) compared to regular and short microcycles. On MD-2, the highest workload was observed in short microcycles, especially for SPD (d = 1.15-1.34). Overall, this study demonstrated that the external and internal load of training sessions vary depending on the length of the microcycles in professional female soccer.